A structure dynamic interaction multiscale method for degradation modeling of bioresorbable polyesters. (October 2021) - Zhang, Taohong; Chen, Han; Guo, Xuxu; Yu, Yixuan; Wulamu, Aziguli
Highlights: Recognition of the interfaces and interactions of different structure phases (amorphous, crystalline and hole phase) are investigated in this paper. Blocked Amorphous (BA), Blocked Cavity (BC) are denoted as the interaction of different structure status phases. Crystal Island, Amorphous Island and Hole Marsh are denoted as the interaction of different strength phases. Boundary Encirclement Algorithm (BEA) is put forward to recognize the interaction of different phases. Based on the recognition of dynamic interaction, the inhomogeneous diffusion of oligomers and chain scission are simulated from local area. Strength model is built from the interaction of amorphous, crystalline and cavity phase. This Structure Pattern Recognition-Multiscale Degradation Model (SPR-MSDM) is developed to simulate the inner interaction of different phases to quantize the material properties during degradation. Abstract: Biomedical degradable polyester materials are widely used in medical field because of their excellent mechanical properties and degradation properties. Analysis of the degradation process and strength change of biomedical degradable materials is essential for clinical use. The evolution of structure from micro to mesoscale is critical for chain broken, recrystallization and macro strength performance during polymer degradation. A structure pattern dynamic interaction method coupled with multi-scale model is proposed in this paper to simulate the degradation process. In the process of status evolution, Blocked Cavity structure pattern (BC pattern) and Blocked Amorphous pattern (BA pattern) are denoted as the interaction of different phases due to their influence on chain scission and oligomer diffusion. In strength structure, Crystalline Island pattern, Amorphous Island pattern and Vacancy Marsh pattern are defined as the interaction to model the strength support. An algorithm named Boundary Encirclement Algorithm (BEA) is designed for the interaction pattern recognition. With the evolution of different phase patterns and the interaction of different phases, chain broken, recrystallization and oligomer diffusion are reconsidered in local area. And strength model is constructed which is based on the interaction of strength patterns. The coupled multiscale model is denoted as Structure Dynamic Interaction-Multiscale Degradation Model (SDI-MSDM). Calculated examples are compared with the experimental data. The simulation value and the experimental value are well fitted, which indicates that the patterns recognition affect the model calculation.